2016
DOI: 10.1037/ccp0000079
|View full text |Cite|
|
Sign up to set email alerts
|

Is supervision necessary? Examining the effects of internet-based CBT training with and without supervision.

Abstract: IBT programs that include supervision may be a scalable and effective method of disseminating CBT into routine clinical practice, particularly for populations without ready access to more-traditional "live" methods of training. There was no evidence for a significant effect of IBT without supervision over a nontraining control, suggesting that merely providing access to IBT programs may not be an effective method of disseminating CBT to routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 38 publications
2
61
1
1
Order By: Relevance
“…Trainees continuing to work in similar workplace settings and see similar patient presentations may assist the consolidation of therapist competence, and contrasts with previous large-scale training initiatives where skill maintenance difficulties were partially attributed to a lack of continuity from training to the work environment (Brooker et al 2003). Therapists' continued use of regular expert supervision may also have supported maintenance of competence (Mannix et al 2006;Rakovshik et al 2016). Therapists however reported reduced use of 'live' supervision (i.e.…”
Section: Clinical Role and Supervisionmentioning
confidence: 95%
“…Trainees continuing to work in similar workplace settings and see similar patient presentations may assist the consolidation of therapist competence, and contrasts with previous large-scale training initiatives where skill maintenance difficulties were partially attributed to a lack of continuity from training to the work environment (Brooker et al 2003). Therapists' continued use of regular expert supervision may also have supported maintenance of competence (Mannix et al 2006;Rakovshik et al 2016). Therapists however reported reduced use of 'live' supervision (i.e.…”
Section: Clinical Role and Supervisionmentioning
confidence: 95%
“…In recent years, multiple trials evaluating different methods of training clinicians to use evidence-based therapies have demonstrated that monitoring and supervision is significantly more effective than workshop-based training alone in a range of therapies (Beidnas & Kendall, 2010; Henggeler, Chapman, Rowland, Sheidow, & Cunningham, 2013; W.R. Miller, Yahne, Moyers, Martinez, & Pirritano, 2004; Schoenwald, Sheidow, & Chapman, 2009), including CBT (Rakovshik, McManus, Vazquez-Montes, Muse, & Ougrin, 2016; Rakovshik et al, 2013; Sholomskas et al, 2005). The lack of supervision and monitoring of clinician implementation of evidence-based treatments in clinical practice suggests that CBT and other EBPs, in practice, may bear little resemblance to the more closely monitored versions of those treatments as implemented in randomized clinical trials demonstrating their efficacy (Martino et al, 2016).…”
Section: Stage 3 and Beyond: Dissemination And Its Challengesmentioning
confidence: 99%
“…Further work should focus on examining whether web-based training is sufficient to change daily working practice. There are hints that the acquisition and implementation of new interventions skills could be limited without case supervision (Edmunds, Beidas, & Kendall, 2013;Miller, Yahne, Moyers, Martinez, & Pirritano, 2004;Rakovshik, McManus, Vazquez-Montes, Muse, & Ougrin, 2016;Sholomskas et al, 2005). Therefore, the investigation of a combination of web-based training and case supervision approach to support therapists in the crucial phase of implementing the learned skills into clinical practice could be a promising starting point for future research.…”
Section: Discussionmentioning
confidence: 99%